1986
DOI: 10.1111/j.1600-0447.1986.tb08990.x
|View full text |Cite
|
Sign up to set email alerts
|

The clinical use of hypnotics: indications for use and the need for a variety of hypnotics

Abstract: Insomnia may be categorized as difficulty falling asleep, frequent awakening, early awakenings or a combination of each. The ideal hypnotic must promote rapid sleep onset and maintain sleep throughout the night while allowing the patient to awake refreshed the following day. Several benzodiazepines, with differing pharmacokinetic and pharmacodynamic profiles are presently available. All are clinically effective and not only elimination half-life but also dosage prescribed and pattern of distribution are import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…The nurses examined in the present study might have preferred to use this drug to treat sleep problems, which were not responsive to other hypnotics. Previous studies have reported that flunitrazepam should be strictly used on a short‐term basis or in those with long‐term insomnia on an occasional basis (Rickels ). Flunitrazepam can easily lead to drug dependence and benzodiazepine withdrawal syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The nurses examined in the present study might have preferred to use this drug to treat sleep problems, which were not responsive to other hypnotics. Previous studies have reported that flunitrazepam should be strictly used on a short‐term basis or in those with long‐term insomnia on an occasional basis (Rickels ). Flunitrazepam can easily lead to drug dependence and benzodiazepine withdrawal syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…17 For instance, midazolam has a half-life of 1-5 hours whereas diazepam concentrations do not fall to 50% until after about 30-60 hours. 18 In general, a shorter acting BZD is preferred over one that may remain in the body for several days or be metabolized to active metabolites. Nighttime dosing with shorter duration agents may lessen the chance of daytime PDI effects.…”
Section: Data Synthesismentioning
confidence: 99%
“…BZDs with longer half-lives may invariably produce carryover effects beyond the dosing period. 17 For instance, midazolam has a half-life of 1 to 5 hours, whereas diazepam concentrations do not fall to 50% until after about 30 to 60 hours. 18 In general, a shorter acting BZD is preferred over one that may remain in the body for several days or be metabolized to active metabolites.…”
Section: Data Synthesismentioning
confidence: 99%
“…Benzodiazepines are among the most commonly prescribed psychotherapeutics, indicated for the treatment of insomnia and anxiety, and as an adjunct treatment for epilepsy and some motor disorders (8,9). Women are significantly more likely to be prescribed a benzodiazepine than men (10).…”
Section: Introductionmentioning
confidence: 99%